THE ROLE OF HANJA IN KOREA: LANGUAGE, SCHOOLARSHIP AND SOCIETY. (Ustozlar uchun, 2026)
This article examines the historical role of 漢字 (Hanja) in Korea, highlighting how it shaped scholarly culture and state administration. Since Korean and Chinese are structurally different, Koreans developed systems such as  향찰 (Hyangchal), and 구결 (Gugyeol) to adapt Chinese characters to Korean grammar and phonology.